Metamemory following childhood brain injury: A consequence of executive impairment. Issue 1 (2nd January 2017) - Geurten, Marie; Chevignard, Mathilde; Kerrouche, Bernadette; Tiberghien, Anne; Meulemans, Thierry
Abstract : In this study, we investigated the influence of children's level of executive functioning on two types of metamemory knowledge following a traumatic brain injury (TBI). For this purpose, 22 children (aged 7 to 14 years) who had sustained a moderate to severe TBI and 44 typically developing children were recruited. The children with TBI were divided into two groups according to the severity of their executive impairment. Injury severity was determined by the Glasgow Coma Scale (GCS) score on admission or by the duration of unconsciousness. All children were then tested on both their knowledge of general memory functioning and their level of memory self-awareness, respectively assessed using the total number of correct responses on an adapted version of a metamemory interview and a self-other discrepancy score on a questionnaire evaluating everyday memory abilities. Data analyses revealed that participants with TBI who suffered impaired executive functions demonstrated less general metamemory knowledge, and underestimated the frequency of their memory problems, compared with children with TBI who had preserved executive functions and with control participants. Considering the well-established effect of metamemory knowledge on people's spontaneous implementation of strategies, the interest and the importance of these findings on both theoretical and clinical grounds are discussed.